A 4-year cross-sectional study on the basic demography and Clopidogrel resistance profile - Besin, Valentinus; Humardani, Farizky Martriano; Notopuro, Paulus Budiono (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Stroke is a leading cause of death and disability worldwide. Clopidogrel is widely used to prevent recurrent strokes in acute ischemic stroke patients, but clopidogrel resistance remains a significant concern due to various factors. While extensive research has been conducted on this issue, data from East Java are limited, and many cases are overlooked by clinicians. This study aimed to address this gap.Methods: We conducted a cross-sectional study involving 108 stroke patients aged 30–80 years who were not using proton pump inhibitors (e.g., omeprazole, esomeprazole) and had been on clopidogrel therapy for at least seven days. Clopidogrel resistance was evaluated using the VerifyNow assay.Results: Out of 108 patients, 27 (25%) were classified as having a bleeding risk. In terms of clopidogrel sensitivity, 79 patients (73%) were sensitive, while 29 (27%) were resistant. Among resistant cases, 17 were male and 12 were female. Age significantly influenced bleeding risk (p = 0.006), but not clopidogrel sensitivity (p = 0.135). Gender had a significant impact on inhibition levels (p = 0.009), as well as on base score (p = 0.009) and PRU score (p = 0.035).Conclusions: A notable proportion of stroke patients in East Java exhibited clopidogrel resistance, with males showing higher resistance rates. Age was a significant factor for bleeding risk, while gender influenced inhibition levels and PRU scores. Further research is needed to explore the underlying reasons for the observed gender differences in clopidogrel resistance.